Ultrasonographic evaluation of thickness and stiffness of achilles tendon and plantar fascia in type 2 diabetics patients: A cross-sectional observation study - Amit Saroha; Sonal Saran; Sudhir Saxena; Ravi Kant; Ajeet Singh Bhadoria (Journal of Medical Ultrasound, 2023)
Background: Diabetes mellitus (DM) can contribute to the development of foot ulcers, a known complication of DM with a high financial and social burden. Achilles tendon (AT) and plantar fascia (PF) are well known to play an important role in foot biomechanics. The present study focuses on the alteration in thickness and stiffness of the AT and PF in Type 2 DM patients compared with the normal controls. Methods: A cross-sectional observational study was conducted with 55 DM patients and 55 healthy volunteers as controls. The thickness of the AT and PF were measured using B-mode ultrasound and stiffness was measured using shear wave elastography. Both the thickness and stiffness in the patient group and controls were compared. The values were also compared with the clinical and demographic profiles of the patients. Results: DM patients had considerably thicker AT and PF than controls (P < 0.05); mean values of AT thickness for DM patients and controls were 5.66 ± 0.54 mm and 4.61 ± 0.39 mm, respectively, and for PF were 2.53 ± 0.51 mm and 1.97 ± 0.19 mm, respectively. Furthermore, the stiffness of AT and PF was significantly (P < 0.05) lower in DM patients compared to controls, suggestive of softening of AT and PF in Type 2 DM patients. Mean values of shear wave velocity for DM patients and controls in AT were 5.53 ± 0.54 m/s and 7.25 ± 0.61 m/s, respectively, and for PF, 4.53 ± 0.89 m/s and 6.28 ± 0.88 m/s, respectively. Conclusion: We conclude that there is softening and thickening of the AT and PF in Type 2 DM patients, which can impair foot biomechanics.